2004
DOI: 10.1093/ajcn/80.5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Diets containing barley significantly reduce lipids in mildly hypercholesterolemic men and women

Abstract: The addition of barley to a healthy diet may be effective in lowering total and LDL cholesterol in both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
148
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(170 citation statements)
references
References 39 publications
7
148
0
9
Order By: Relevance
“…In the first study by Behall et al (2004a), the medium dose (3 g) of barley b-glucans significantly lowered the total and LDL concentrations compared to the low dose. This did not occur in the second study (Behall et al, 2004b). Keogh et al (2003) also recently investigated the serum lipoprotein profile in hypercholesterolaemic men taking barley b-glucans, but did not see any significant effect compared to control of a daily 10 g dose of barley b-glucans incorporated into foods as bread, cakes, muffins or savoury dishes.…”
Section: Introductionmentioning
confidence: 93%
“…In the first study by Behall et al (2004a), the medium dose (3 g) of barley b-glucans significantly lowered the total and LDL concentrations compared to the low dose. This did not occur in the second study (Behall et al, 2004b). Keogh et al (2003) also recently investigated the serum lipoprotein profile in hypercholesterolaemic men taking barley b-glucans, but did not see any significant effect compared to control of a daily 10 g dose of barley b-glucans incorporated into foods as bread, cakes, muffins or savoury dishes.…”
Section: Introductionmentioning
confidence: 93%
“…The protective effects of dietary fiber against cardiovascular disease (CVD), mediated through a reduction in serum lipids, were first reported 440 years ago by Keys et al (1960); later research led to the dietary fiber hypothesis proposed by Burkitt et al (1974) and Trowell (1975) that states that a high intake of starchy carbohydrates and fiber is protective against CVD. Many trials showed a hypocholesterolemic effect of an increased intake of fiber from cereals, such as barley, rice and oats; the active component in barley has been identified as beta-glucans, which reduces serum total cholesterol by 5-10% (according to Anderson, 1987;McIntosh et al, 1991;Shimizu et al, 2008;Talati et al, 2009) and by 20% (according to Behall et al, 2004), although not all studies (Keogh et al, 2003) showed barley beta-glucans to be hypocholesterolemic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, feeding fiber supplements to diabetic animals reduces nutrient absorption [1,2]. In humans, dietary fiber has been used to reduce the blood concentrations of cholesterol and triglycerides [3,4], presumably acting to reduce the intestinal absorption of lipids. Similarly, long-term feeding studies incorporating viscous soluble fiber in the form of β-glucan have demonstrated reductions in plasma cholesterol concentrations in hypercholesterolemic men [5,6].…”
Section: Introductionmentioning
confidence: 99%